2020
DOI: 10.5194/aab-63-345-2020
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism and molecular characteristics of the <i>CSN1S2</i> gene in river and swamp buffalo

Abstract: Abstract. The αS2-casein (αS2-CN) is a member of the casein family associated with milk traits in ruminants, but so far the buffalo CSN1S2 gene has not been well understood. In this work, the polymorphisms of CSN1S2 in river and swamp buffalo were detected using direct sequencing of polymerase chain reaction (PCR) products. As a result, 13 single nucleotide polymorphisms (SNPs) were identified in the coding sequence (CDS) of CSN1S2 in two types of buffalo, of which eight SNPs were non-synonymous. The amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Comparative amino acid sequence analysis revealed that CN protein harbor higher amino acid variations in river buffalo (Mediterranean and Murrah) as compared to the swamp buffalo. The results of the present study are in line with previous studies (Masina et al, 2007;Azevedo et al, 2008;Massella et al, 2017;Rangel et al, 2017;Miluchova et al, 2018;Fan et al, 2020;de Oliveira et al, 2021) which reported the potential association of genetic variants in CSN genes with lactation performance, milk composition, and attributes of milk products. Thus, casein gene-based markers are important candidates for the selective breeding of buffalo to improve the quantity and quality of milk (de Oliveira et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Comparative amino acid sequence analysis revealed that CN protein harbor higher amino acid variations in river buffalo (Mediterranean and Murrah) as compared to the swamp buffalo. The results of the present study are in line with previous studies (Masina et al, 2007;Azevedo et al, 2008;Massella et al, 2017;Rangel et al, 2017;Miluchova et al, 2018;Fan et al, 2020;de Oliveira et al, 2021) which reported the potential association of genetic variants in CSN genes with lactation performance, milk composition, and attributes of milk products. Thus, casein gene-based markers are important candidates for the selective breeding of buffalo to improve the quantity and quality of milk (de Oliveira et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Buffalo is a luxurious genetic resource with multiple utilities (as a dairy, draft, and meat animal) and economic significance in the tropical and subtropical regions of the globe ( Rehman et al, 2019 , 2020 ; Luo et al, 2020 ). The domesticated buffalo is grouped into river buffalo with karyotype 2n = 50 primarily present in southwestern Asia, India, south Mediterranean Europe, and Egypt and swamp buffalo with 2n = 48 distributed across Southeast Asia, southern and southeast China, where the swamp buffalo is used as draft power in the rice paddy fields while the river buffalo is mainly reared for milk production ( Moioli et al, 2001 ; Fan et al, 2020 ; Luo et al, 2020 ). The excellent potential to survive and perform on marginal resources under harsh environmental conditions makes buffalo an important source for nutritious products, particularly milk and meat.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the CSN1S2 gene, the coding sequence of river and swamp buffaloes, 13 SNPs were identified, including 8 non-synonymous substitutions. The amino acid variations due to c.580T > C and c.642C > G might have a physiological impact on the αS2-CN synthesis and ultimately the milk yield in buffaloes [ 120 , 121 ].…”
Section: Identification Of Genes Affecting Important Buffalo Traitmentioning
confidence: 99%